2016
DOI: 10.1128/mcb.00380-16
|View full text |Cite
|
Sign up to set email alerts
|

SIK2 Restricts Autophagic Flux To Support Triple-Negative Breast Cancer Survival

Abstract: c Triple-negative breast cancer (TNBC) is a highly heterogeneous disease with multiple, distinct molecular subtypes that exhibit unique transcriptional programs and clinical progression trajectories. Despite knowledge of the molecular heterogeneity of the disease, most patients are limited to generic, indiscriminate treatment options: cytotoxic chemotherapy, surgery, and radiation. To identify new intervention targets in TNBC, we used large-scale, loss-of-function screening to identify molecular vulnerabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Hypertrophic chondrocytes and the bone major function of SIK3 is to serve as a protein kinase. Small-molecule SIK inhibitors have been studied as research tools and potential therapeutic agents for cancer (72)(73)(74)(75), inflammatory bowel disease (76), skin pigmentation (28), and osteoporosis (29). Our current in vivo results indicate that a major biologic action of SIKs is to mediate multiple biologic actions of PTH1R signaling.…”
Section: Discussionmentioning
confidence: 89%
“…Hypertrophic chondrocytes and the bone major function of SIK3 is to serve as a protein kinase. Small-molecule SIK inhibitors have been studied as research tools and potential therapeutic agents for cancer (72)(73)(74)(75), inflammatory bowel disease (76), skin pigmentation (28), and osteoporosis (29). Our current in vivo results indicate that a major biologic action of SIKs is to mediate multiple biologic actions of PTH1R signaling.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, SIK2 was associated with better survival in renal and liver cancer patients [ 35 ]. In contrast, SIK2 was proposed to support survival of TNBC cells with claudin-low subtype via limiting autophagic influx [ 33 ]. Since SIK2 was previously suggested as an important modulator of autophagosome maturation [ 27 ], its role in cancer cell survival through regulating autophagy requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Liu group indicated that overexpression of miR-203 sensitized Taxol resistant colorectal cancer cells via targeting SIK2 [ 32 ]. In another study, increased autophagic flux into TNBC cells was achieved by blocking of SIK2 [ 33 ]. Miranda and colleagues demonstrated that SIK2 contributes to ovarian tumor metastasis by localizing to the adipocyte rich environment to support survival and metabolic requirements of the cells [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…To analyze its role in autophagy, WNK1 was knocked down with small interfering RNA (siRNA) in U2OS cells stably expressing green fluorescent proteintagged light chain 3 (GFP-LC3) (32,45). WNK1 depletion increased the number of GFP-LC3 puncta ( Fig.…”
Section: Wnk1 Depletion Increases Autophagymentioning
confidence: 99%